The British Critical Tradition
XI, 257 p.
Keywords: This collection offers a reinterpretation of the history of British criticism by exploring the work of neglected as well as celebrated critics. It contextualizes the current crisis and shows how traditional criticism anticipates and to some extent parallels the concerns of postmodern critical theory. The issue of value is also addressed as is the question of the future direction of criticism making this volume an important contribution to contemporary critical debate.